Philosophical approaches to the study of literature - Hogan, Patrick Colm (University Press of Florida, 2000)
Beginning with Greek, Arabic, and Sanskrit classics, Hogan explains the philosophical work that has been crucial to literary theory, moving through Kant and the German Idealists (Fichte, Schelling, Hegel) and post-Idealists (Nietzsche, Marx), to phenomenology, hermeneutics, and the recent European schools (Foucaultian historicism, structuralism, deconstruction, and so on). He also presents the Anglo-American tradition, from logical positivism to Wittgenstein and the Ordinary Language theorists, from Chomskyan linguistics to cognitive science and philosophy of science. Beyond the founding principles and general structure of these theories, Hogan illustrates their practical application and value with interpretive discussions of Othello and Agha Shahid Ali's "I Dream It Is Afternoon When I Return to Delhi."